Public Transport Passenger Satisfaction in Surabaya Using Ordinal Logistic Regression and Importance Performance Analysis - Azzahro, Amilia; Chamid, Mutiah Salamah; Azizah, Nur (IPTEK, DRPM, Institut Teknologi Sepuluh Nopember, 2023)
Public transportation has an important role in everyday life, namely reducing congestion and avoiding traffic accidents. However, in reality, public transportation tends to be abandoned by the people of Surabaya. The tendency of public transportation to be abandoned by the people of Surabaya City is due to reduced public satisfaction with the quality of public transportation services. This study aims to determine the factors that affect the satisfaction of public transport passengers in the city of Surabaya using Ordinal Logistics Regression and identify what service quality needs to be improved and maintained in urban transportation using the Importance Performance Analysis method. The results of this study indicate that 70% of public transport passengers in Surabaya are dissatisfied with the quality of the public transportation service. Variables that affect passenger satisfaction are reliability (the ability of the public transportation to provide the promised service immediately), responsiveness (the ability of the driver to assist passengers and provide responsive and fast service), assurance (the knowledge and ability of the driver to maintain passenger trust), empathy (care driver to passenger needs), direct evidence (passenger attractiveness to the physical facilities of the public transportation), and transportation fares. The service quality variable that becomes the main priority for improvement is the ability of the driver to provide the promised service immediately, the knowledge, ability, courtesy and safety of the driver in carrying out their duties as well as attractiveness to physical facilities.